Notes on the genus Polycaena Staudinger (Lepidoptera: Riodinidae) with descriptions of two new species from China - Huang, Hao; Li, Yu-Fei (Zootaxa, 2016)
Polycaena sejila sp. n. (Riodinidae: Nemeobiinae: Nemeobiini: Nemeobiina) and P. wangjiaqii sp. n. are described from Tibet Autonomous Region and Yunnan province respectively. P. lua minor is raised to full species, namely P. minor stat. n.; P. lama qinghaiensis syn. n. is recognized as a new junior synonym of P. kansuensis; P. lama taibaiensis is transferred as a subspecies of P. lua, namely P. lua taibaiensis stat. n.. The male genitalia of P. sejila, P. wangjiaqii, P. lama, P. kansuensis, P. lua lua, P. lua taibaiensis and P. minor are described and illustrated. A checklist of the genus Polycaena is updated and a key to species of the genus is provided.